If it's not what You are looking for type in the equation solver your own equation and let us solve it.
b/3=-11
We move all terms to the left:
b/3-(-11)=0
We add all the numbers together, and all the variables
b/3+11=0
We multiply all the terms by the denominator
b+11*3=0
We add all the numbers together, and all the variables
b+33=0
We move all terms containing b to the left, all other terms to the right
b=-33
| 11=2b=17 | | 4x-7+6x+5=48 | | a1/4-+21/2=4 | | 10(1/3n-4=3/4n+1) | | 56+4y-25=16y-11-5y | | -2=-w/8 | | 3(2/3(x+6)=2/3x+4) | | 4y=8×-2 | | 7+b/4=11 | | 4|w+7=22 | | 9y-6=1 | | (1/2)x=4(2/3)x+1 | | 60x-35=10x+35 | | 121/400=d^2 | | |2x+8|=x+4 | | a4−56=−12 | | 3.7w-11=4.7w | | 31x+40=10+2x | | 2^(3-x)+2^(x+2)=33 | | (3x+4)+50=90 | | 7-2(4-3n)+8n=-(n+31) | | -8y=42-y | | 5x+6(2+3x)=35 | | 7/4+4m/9=91/36 | | 5670=3w^2 | | 4x=20(x-10) | | 7-x=42 | | 40=p(0.04)(2) | | .16-7d=-3d+2 | | 64/4=d^2 | | -10y+18=-15–21+5y | | 2=2(b-17) |